2023
DOI: 10.3847/1538-4357/acdc1f
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Gravity Waves in the Middle and Upper Atmosphere of Mars Based on ACS/TGO Observations

Abstract: Gravity waves (GWs) are important for the vertical coupling of the Martian atmosphere. The middle atmosphere is the key region where GWs propagate to the upper thermosphere and generate momentum and energy exchange, but the knowledge of middle-atmosphere GWs is incomplete, due to the lack of observations with the kilometer-scale resolution. We have analyzed the climatology of GW activity in the middle and upper atmosphere of Mars using 20–180 km temperature profiles measured by the Atmospheric Chemistry Suite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ji et al (2022) also suggested an association between N 2 being less than zero and GWB on Mars, so we calculate Brunt-Väisälä frequencies (N) based on neutral atmospheric CO 2 density and take N 2 less than zero as an index of GWB. The calculation methods are used by Manju and Mridula (2020) and Ji et al (2022Ji et al ( , 2023, and the specific procedure is as follows.…”
Section: Calculation Of the Brunt-väisälä Frequencymentioning
confidence: 99%
“…Ji et al (2022) also suggested an association between N 2 being less than zero and GWB on Mars, so we calculate Brunt-Väisälä frequencies (N) based on neutral atmospheric CO 2 density and take N 2 less than zero as an index of GWB. The calculation methods are used by Manju and Mridula (2020) and Ji et al (2022Ji et al ( , 2023, and the specific procedure is as follows.…”
Section: Calculation Of the Brunt-väisälä Frequencymentioning
confidence: 99%
“…That database covered observations for 1.5 Martian years (MYs), from the middle of MY 34 to the end of MY35. The same volume of the ACS-MIR/TGO data was recently analyzed by Ji et al (2023) applying another algorithm of extracting wave components.…”
Section: Introductionmentioning
confidence: 99%